4+9xy-18y-2x=

Simple and best practice solution for 4+9xy-18y-2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+9xy-18y-2x= equation:


Simplifying
4 + 9xy + -18y + -2x = 0

Reorder the terms:
4 + -2x + 9xy + -18y = 0

Solving
4 + -2x + 9xy + -18y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -2x + 9xy + -4 + -18y = 0 + -4

Reorder the terms:
4 + -4 + -2x + 9xy + -18y = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -2x + 9xy + -18y = 0 + -4
-2x + 9xy + -18y = 0 + -4

Combine like terms: 0 + -4 = -4
-2x + 9xy + -18y = -4

Add '18y' to each side of the equation.
-2x + 9xy + -18y + 18y = -4 + 18y

Combine like terms: -18y + 18y = 0
-2x + 9xy + 0 = -4 + 18y
-2x + 9xy = -4 + 18y

Reorder the terms:
4 + -2x + 9xy + -18y = -4 + 18y + 4 + -18y

Reorder the terms:
4 + -2x + 9xy + -18y = -4 + 4 + 18y + -18y

Combine like terms: -4 + 4 = 0
4 + -2x + 9xy + -18y = 0 + 18y + -18y
4 + -2x + 9xy + -18y = 18y + -18y

Combine like terms: 18y + -18y = 0
4 + -2x + 9xy + -18y = 0

The solution to this equation could not be determined.

See similar equations:

| (w-4)/6 | | -5(5y-7)+3(2y+6)= | | 15x^2-10x-6=0 | | 8-x+4-2-8x= | | -4(5y-6)+3(3y+10)= | | (-a-5b+4)2ab= | | 12y+7y= | | (2a-5b)(2a+5b)=0 | | f(26)=13 | | 8x+14=2x+22 | | 5-x=x+13 | | -x-15y=-25 | | 8/64-2/x | | 8/62-2/x | | 4b^2-7m-13=-10 | | 5x+3y=420Y | | 5/2*x=10 | | 4b^2-7m-13=10 | | 20(x)+50(y)=1100 | | 4b^2-7m-13=0 | | 57(67)653= | | -10a=70 | | 20+5y=30 | | 5u+3w=4u+6w | | n(n+4)=96 | | n^2-8=80 | | (7e^3x)-5=23 | | (3m^2(n))(-2mn^3)+((m^3)n^4)-5n^4=0 | | f(x)=cos(x) | | (3m^2(n))*((-2mn^3)+((m^3)n^4)-5n^4)=0 | | (3m^2(n))((-2mn^3)+((m^3)n^4)-5n^4)=0 | | (x+3)+(8-5x)= |

Equations solver categories